2016
DOI: 10.1111/gcb.13448
|View full text |Cite
|
Sign up to set email alerts
|

Irrigating grazed pasture decreases soil carbon and nitrogen stocks

Abstract: The sustainability of using irrigation to produce food depends not only on the availability of sufficient water, but also on the soil's 'response' to irrigation. Stocks of carbon (C) and nitrogen (N) are key components of soil organic matter (SOM), which is important for sustainable agricultural production. While there is some information about the effects of irrigation on soil C stocks in cropping systems, there is a paucity of such studies in pastoral food production systems. For this study, we sampled soils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 41 publications
3
40
0
1
Order By: Relevance
“…3,4), by stimulating soil microbial activity (e.g., N mineralization, N nitrification, and litter decomposition; Aerts 1997, Wang et al 2006, Schaeffer et al 2013. However, water addition could diminishingly stimulate productivity over time if water addition results in decreased soil N availability because water addition likely increases N losses (Yahdjian and Sala 2010), e.g., through denitrification and leaching (Mudge et al 2016). Our experiment included the combined addition of water and N, and showed that productivity was persistently increased by water only when N was also added (Fig.…”
Section: Mechanisms By Which Increased Precipitation Influences Produmentioning
confidence: 99%
“…3,4), by stimulating soil microbial activity (e.g., N mineralization, N nitrification, and litter decomposition; Aerts 1997, Wang et al 2006, Schaeffer et al 2013. However, water addition could diminishingly stimulate productivity over time if water addition results in decreased soil N availability because water addition likely increases N losses (Yahdjian and Sala 2010), e.g., through denitrification and leaching (Mudge et al 2016). Our experiment included the combined addition of water and N, and showed that productivity was persistently increased by water only when N was also added (Fig.…”
Section: Mechanisms By Which Increased Precipitation Influences Produmentioning
confidence: 99%
“…The SOC associated with the fine fraction is relatively resistant to changes in management (Campbell, Zentner, Bowren, Townley‐Smith, & Schnitzer, ; Chung, Grove, & Six, ; Skjemstad, Spouncer, Cowie, & Swift, ) and is characterized by long turnover times (Balesdent, Besnard, Arrouays, & Chenu, ; Buyanovsky, Aslam, & Wagner, ). However, intensive management can result in losses of C (Mudge et al., ; Schipper et al., ) from the fine fraction (Gregorich et al., ) leaving a deficit of stable C that may be filled with the use of appropriate sequestration practices.…”
Section: Introductionmentioning
confidence: 99%
“…One site in the Canterbury region was sampled to only 0.3 m due to high stone content lower in the profile. The selection criteria considered when choosing sampling locations have been fully described by Mudge et al (2016) along with further information on irrigation duration (ranging 3-20 years), soil orders, type of irrigation and long-term climate data for each sampling site. The irrigated and unir rigated areas within a field were identified using local knowledge, Google Earth imagery, Irrigation Resource Consents and help from rural professionals (Mudge et al, 2016).…”
Section: Site and Soilmentioning
confidence: 99%
“…Soils and topography were the same between irrigated and unirrigated areas, and 4. Farm management (such as fertilizer application) was the same in irrigated and unirrigated areas (expect for irrigation) (Mudge et al, 2016).…”
Section: Site and Soilmentioning
confidence: 99%
See 1 more Smart Citation